2018
DOI: 10.1371/journal.pone.0204179
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation on the tribological performance of ring/liner system under cylinder deactivation with consideration of cylinder liner deformation and oil supply

Abstract: In gasoline engines, CDA (cylinder deactivation) affects greatly the tribological performance of ring/liner system while reducing the emissions and improving the fuel economy. The analyses on the tribological performance of ring/liner system under the CDA mainly focus on the ideal circular cylinder liner and fixed fully flooded lubrication condition. In this study, a numerical investigation on the tribological performance of a compression ring-cylinder liner system is presented under the CDA with consideration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…S. Bewsher et al [27] found that the total frictional loss under CDA is 9.53% higher than that under normal operation. Similar results have been achieved in [28][29][30]. However, a decrease in the overall frictional loss under CDA operation has been reported in [31,32].…”
Section: Introductionsupporting
confidence: 88%
“…S. Bewsher et al [27] found that the total frictional loss under CDA is 9.53% higher than that under normal operation. Similar results have been achieved in [28][29][30]. However, a decrease in the overall frictional loss under CDA operation has been reported in [31,32].…”
Section: Introductionsupporting
confidence: 88%
“…The liner can be deformed from its ideal circular shape due to several processes, such as manufacturing tolerances, assembly load of the cylinder head and cylinder head gasket, thermal expansion variations between cylinder block and cylinder head, gas pressure during fire operations, temperature gradients during fire operations, and mechanical load during fire operations. 913 It was shown that operational thermal and mechanical load contributes more than 85% of the total liner deformation. 9 The prediction of the shape, the path, and the magnitude of this deformation is extremely important in any design improvement in order to reach a better engine performance.…”
Section: Introductionmentioning
confidence: 99%
“…He obtained a generalized expression for bore distortion and identified it as a criterion of piston ring conformability. Also, Lu et al 10 analyzed the tribological performance of the ring–liner system under cylinder deactivation considering the cylinder liner deformation and the change in oil supply. They used the Fourier series decomposition of the liner shape with fourth-order deformations (n = 4) to model the shape of the deformed liner, since lower order (n = 2) is completely accommodated by the elastic deformation of the compression ring.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of the effect of cylinder liners on friction, in [29], the authors studied that the friction of cylinder linerpiston ring reduces due to the impact of combustion shock excitation and piston side force. Lu et al [30] studied the effect of cylinder deactivation on the friction performance of cylinder liner.…”
Section: Introductionmentioning
confidence: 99%